1989
DOI: 10.1159/000177521
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Selenium Toxicity in Guinea Pigs: Biochemical Studies

Abstract: Biochemical studies were conducted in experimentally induced selenium toxicity in recently weaned guinea pigs. A significant drop in blood glucose level, in comparison to controls, was observed in animals fed selenium-enriched barley (organic form) as well as those fed ordinary barley mixed with sodium selenite (inorganic form). Estimation of total serum proteins also revealed a significant drop in both these groups. SGOT (EC 2.6.1.1) activity was comparatively lower but no significant alteration was noticed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The resultant hypoproteinaemia in the selenium treated birds was possibly because of its decreased synthesis by the degenerated and / or necrotic liver which was evident in necropsy finding. Similar finding were also reported by Das et al (1989b) in the selenium treated birds. It was found that considerable elevation in the values of BUN in the birds of group A as compared to group B and C birds, but the difference were not significant.…”
Section: Lungssupporting
confidence: 91%
“…The resultant hypoproteinaemia in the selenium treated birds was possibly because of its decreased synthesis by the degenerated and / or necrotic liver which was evident in necropsy finding. Similar finding were also reported by Das et al (1989b) in the selenium treated birds. It was found that considerable elevation in the values of BUN in the birds of group A as compared to group B and C birds, but the difference were not significant.…”
Section: Lungssupporting
confidence: 91%
“…For example, selenium and zinc levels in Taiwan and Bangladesh are among the lowest worldwide ( Lin and Yang 1988 ), and poor dietary selenium has been suggested as an underlying factor for arsenic and cancer in Bangladesh and West Bengal in India ( Spallholz et al 2004 ). In guinea pigs, selenium and arsenic counteract each other in glucose metabolism ( Das et al 1989 ), and the joint effect of high arsenic and low selenium could play a role in diabetes development. Exposure to arsenic, selenium, other nutrients, and other diabetes risk factors were not measured in epidemiologic studies.…”
Section: Discussionmentioning
confidence: 99%